Fingermittelgelenkfrakturen: Diagnostik und operative Therapiemöglichkeiten = Fractures of the proximal interphalangeal joint : diagnostic and operative therapy options - Unglaub, Frank (Der Unfallchirurg, 2016)
Joint fractures of the fingers often entail operative interventions in contrast to extra-articular fractures. These types of fracture are inclined to dislocate in addition to the actual fracture. The proximal interphalangeal (PIP) joint in particular often shows comminuted fractures due to the long leverage of the finger and a relatively small diameter of the joint. The clinical examination, X-ray diagnostics and if necessary computed tomography allow the classification into stable and unstable fractures. Unstable fractures must be treated by surgical reduction and fixation. A multitude of operative techniques are available for these mostly complicated fractures. The foremost goal is a stable osteosynthesis of the fracture with repositioning of the dislocation, which enables early physiotherapy in order to prevent tendon adhesion and contracture. This article presents the different types of PIP joint fractures, their specific surgical treatment and postoperative treatment regimens.